IMPLEMENTASI SPOTIFY BAGI GRUP MUSIK INTHESKY BAND DI MEDAN SUMATERA UTARA - Tarigan, Furnita Giovani; Ginting, Pulumun; Sihombing, Lamhot; Hirza, Herna (Universitas Negeri Medan, 2020)
This study aims to find out about the implementation of spotify for the band Inthesky Band in Medan, North Sumatra. This study uses theories related to research topics such as the meaning of implementation, the meaning of spotify, social media theory, the meaning of applications, the meaning of musical groups, and theory of results. The population in this study are eight music groups consisting of Inthesky Band, Garside, Shadowplay, Psychotic Villager, Boxquitos, Pesawat Sederhana, Moove, and Equaliz. Based on the results of research conducted, the Inthesky Band music group uses Spotify to introduce their musical works to the public. Spotify is one of the most widely known digital music platforms and is used in the digital era today, especially by young people and music lovers who love indie music. In implementing Spotify, the Inthesky Band music group started by compiling the concept of a song that they wanted to make, then producing it into a song that is ready to be played through Spotify by using one of the service providers, namely Netrilis. The results of the implementation of spotify for the Inthesky Band music group have a good impact on the music group itself as well as for connoisseurs, including Exposure which is how the songs of the Inthesky Band music group are increasingly heard by people and spread widely through social media networks that Share songs from Inthesky Band, Inthesky Band music groups can see the development of their own music groups, can get royalties and Inthesky Band music groups are able to be in the same playlist as National musicians. For music lovers, it's easier to access songs from Inthesky Band through Spotify which are available in paid or free form and for others musicians to be motivated to do the same, create music using Spotify.